LGBTQ+ veterans file civil rights suit against Pentagon over discriminatory discharges - Kegu, Jessica; Axelrod, Jim; Samu, Shewna (CBS News, 2023)
A group of LGBTQ+ veterans who were kicked out of the military because of their sexual orientation filed a federal civil rights suit on Tuesday over the Defense Department's failure to grant them honorable discharges or remove biased language specifying their sexuality from their service records following the repeal of "don't ask, don't tell" in 2010.
United States of America
Keywords: 2023-08 August; Class action; Veterans